Parental preferences for the procedural sedation of children in dentistry: a discrete choice experiment - Zhuge, Jinru; Zheng, Dongyue; Li, Xingwang; Nie, Xin; Liu, Jiefan; Liu, Ruohai (Frontiers in Pediatrics, 2023)
Purpose: The aim of this study was to explore parental preferences for the procedural sedation of children in dentistry through a discrete choice experiment (DCE) to inform clinical decisions and oral health management. Methods: Based on literature reviews, interviews with parents of pediatric dental patients, and expert consultation, six attributes, including fasting time, recovery time, sedative administration routes, adverse reactions, sedation depth and procedure cost, were incorporated into the DCE questionnaire. The DCE questionnaire collected data on parental preferences for pediatric dental sedation treatment from June to August 2022. A conditional logit model was used to analyze preference and willingness to pay (WTP) for each attribute and its level. Subgroup analyses assessing the impact of parents' dental anxiety on procedural sedation preferences were also conducted using conditional logit models. Results: A total of 186 valid questionnaires were gathered. Parents’ preferences for fewer adverse reactions, a milder sedation depth, lower out-of-pocket cost, shorter fasting and recovery times and administration by inhalation were significantly associated with their choice of sedation model. The conditional logit model showed that parents were most interested in treatments with no adverse reactions (0%) (vs. 15%) (Coef, 1.033; 95% CI, 0.833 to 1.233), followed by those providing minimal sedation (vs. deep sedation) (Coef, 0.609; 95% CI, 0.448 to 0.769). Moreover, the relative importance of adverse reactions and fasting time was higher among anxious than nonanxious parents. The study found a WTP threshold of ¥1538 for reducing adverse reactions (15% to 0%). The WTP threshold for the best sedation procedure scenario (no fasting requirement, 10 min recovery time, administration by inhalation, 0% adverse reaction incidence and minimal sedation) was ¥3830. Conclusion: Reducing the adverse reactions and depth of sedation are predominant considerations for parents regarding procedural sedation in pediatric dentistry, followed by lower cost, shorter fasting and recovery times and inhalation sedation. Parents with dental anxiety had a stronger preference for options with a lower incidence of adverse reactions and shorter fasting time than parents without dental anxiety. This discovery is helpful for doctors and can promote collaborative decision-making among parents and doctors.